A pr??tica teatral no ensino m??dio p??blico: entre resson??ncias e resist??ncia - Pereira, Priscila Cassanti Sil (2018)
This research approaches the theatrical practice in high school and is based on bibliographical, documentary an empirical research, by interviewing five teachers from the public schools in the state of S??o Paulo. During the study development, the research aimed to stablish the theatrical practices used by the teachers interviewed and to know, through the interviews, the reflexes of theatrical practice in the students, according to the teachers??? perception. Besides that, the research also intended to inquire whether Law n?? 13.278/16 is discussed in the schools where the interviews were conducted. The starting point for this proposal was caused by concerns about manifestations observed in the daily life between different people and in the media, such as acts of physical and symbolic violence???s. The observed hypothesis is that the practice provides a way to sensitize the young people in their formation. The theoretical reference of the work is the complex thought, of Edgar Morin, evidencing the categories esthetic and poetic states to think on the human formation. The analyzes of the interviews showed that the theatrical practice provokes transformation in the students, entitled as resonances in the present work. Fifteen qualities of resonance were observed in the students who worked with the theatrical activity. Among them stands out the sensitivity, explained in this dissertation as a guiding thread of perceptions between the inner and outer world. The interviewees also related four specific difficulties of performing theatrical practice and linked to the school environment. The analyzes also showed that the theater practice happens independently of Law n?? 13.278/16, driven by students resistance force and mobility, reverberating in teachers, crossing the walls of schools.